PENENTUAN NILAI SPF (SUN PROTECTION FACTOR) KRIM EKSTRAK ETANOL BUNGA TELANG (CLITORIA TERNATEA) SECARA IN VITRO MENGGUNAKAN METODE SPEKTROFOTOMETRI - Dian Puspitasari; Diah Pratimasari; Disa Andriani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Indonesia is a tropical country with high sun exposure. High sun exposure can cause several problems with the skin, ranging from reddish skin, pigmentation, and even for a long time can cause cancer risk. One way to reduce the negative impact of sun exposure by using sunscreen. Telang flowers are rich in bioactive compounds such as phenolic compounds, especially flavonoids, which have the potential to be used as sunscreens. This study aims to determine the optimal concentration of telang flower extract on sunscreen cream based on physical properties and SPF values.Telang flowers are extracted macerated using 70% ethanol, then the obtained Telang flower extract (EBT) is formulated into a sunscreen cream with various concentrations. Various EBT concentrations on sunscreen creams were tested for physical stability and their effectiveness based on SPF values. The data obtained were analyzed statistically by ANOVA using the T-test with a confidence level of 95%. From this study, the optimum concentration of telang flower extract was found to be 5% contained in Formula III sunscreen cream.